Assessment of quality of life of patients after resection of gallbladder with laparoscopic and traditional method - Paweł Węgorowski; Agnieszka Antoniewska; Renata Domżał-Drzewicka; Marcin Rząca; Joanna Michalik (Kazimierz Wielki University, 2018)
Admission Cholelithiasis is one of the most common conditions in the abdominal cavity. The highest incidence is observed in highly developed or developing countries. Bile duct diseases often require surgical treatment, which is a great physical and mental burden for the patient. The perspective of the surgical procedure and the accompanying circumstances is a sense of insecurity and fear for the patient and his family. The fact of the prevalence of cholelithiasis and the effects of the disease may have an impact on the quality of life of people after gallbladder surgery. Objective of the work The aim of the study was to assess the quality of life of patients after resection of the gall bladder using laparascopy and traditional methods. Research methods As a research method, the diagnostic survey method was used, a standardized WHOQOL-BREF questionnaire was used, in which the analysis of the collected material referred to the somatic, psychological, social and environmental sphere. Results The obtained research results allowed to state that socio-demographic variables differentiated the patients' opinions on the subjective assessment of the quality of life and health. The place of residence does not have a significant impact on the quality of life. Key words: quality of life, gall bladder resection